GENERAL DESIGN SISTEM INFORMASI PENGGAJIAN BERBASIS POINT SYSTEM DENGAN METODE WATER FALL - Muhammad Taufiq; Sarmidi; Cecep Riki; Nandhini Hudha Anggarasari; Iva Afifah; Utari Nur Ambiya; Dzaky Muhammad Nur Waffi; Rifqi Aminullah (Universitas Majalengka, 2021)
Starting from problems that often arise in a company or agency regarding the payroll system, whether it is in the form of errors in salary management, calculation methods or patterns of determining the amount of employee salaries, resulting in a work atmosphere that is less conducive and less harmonious between employees in the management environment, as a result it occurs. decrease in employee motivation (demotivation), with the number of complaints, lethargy and suspicion of employees, both in functional and structural relationships. This kind of condition will have a direct impact on morale which can have fatal consequences for the company's continuity. For It, For It, For It Is The Expedors, About Transparent and Accountable Payroll System. Transparent in the sense that it is wide open based on the method of determining or calculating the salary of each employee based on a standardized formulation, where everything will be computerized based on an appropriate point system. The accountable means being accountable for the results obtained in an Information Technology-based payroll information system.